Extending deontic interpreted systems with action logic - Barbosa, Raquel de Miranda; Costa, Antônio Carlos da Rocha (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
This paper presents an extension to deontic interpreted systems with the use of action logic for the specification of normative aspects in multiagent systems. The paper presents a preliminary formalization of operators required and describes a simple example of the application of this formalization, using the segregation model (a simulation model available in NetLogo platform) through the formalization and proof of some properties of this system.